Library wars. 8, Love & war - Yumi, Kiiro (Shojo beat manga., 2012)
Iku Kasahara has dreamed of joining the Library Defense Force ever since one of its soldiers stepped in to protect her favorite book from being confiscated in a bookstore, but now that she's a recruit, her dream job is more like a nightmare.